Avaliação bioeconômica da suplementação de bovinos e ovinos em pastagens de Brachiaria brizantha cv. Marandu e Xaraés - Carvalho, Daniel Marino Guedes de (2011)
The objective of this study was to evaluate the effects of supplementation on the productive response, pH, ruminal ammonia nitrogen, cost of production and behavior of grazing beef cattle and sheep grazing grass Marandu and productive response and cost of production of dairy cows Xaraés grass pasture. Two experiments were conducted with sheep, one with two beef cattle and dairy cows. In the first experiment we used 20 non-castrated lambs with age and initial body weight average of four months and 24.20 kg, respectively, to evaluate the average daily gain weight and production cost, according to the following supplements: mineral, energy , multiple and protein, provided to 0.105 kg animal day-1 for the lambs during the dry season. Simultaneously with the performance experiment four animals were kept in the rumen cannulated with 12 months and 55.00 kg of body weight, respectively, distributed in four paddocks of 0.1 ha provided with water fountains and troughs, undergo the same treatments. In the second experiment, 20 lambs were used to age and initial body weight average of four months and 21.73 kg, respectively, to evaluate supplements based on minerals and soybean meal, soybean and cottonseed, provided to 0.250 g animal-1 day for lambs in the period of water and water-dry transition, and the mineral mixture provided ad libitum. In the third experiment 20 bulls were used with age and baseline body weight of 10 months and 172 kg, respectively, conducted in the experimental area consists of four paddocks of 1.45 ha. Animal was given 1.0 kg day-1 of supplement concentrated, with a mineral mixture provided ad libitum. The animals were weighed at the beginning and end of the experiment, to determine the daily weight gain. The fourth experiment was conducted with dairy cows with average weight of 460 kg, being conducted at the experimental area consists of five paddocks of 0.45 ha, with the grass Xaraés formed, provided with water fountains and troughs covered, and for five periods of 14 days, totaling 70 days of experimental periods in water. The treatments consisted of providing supplements and multiple energy supplied to 2 and 4 kg animal day, plus an additional witness (mineral mixture) provided ad libitum. The fifth experiment was conducted in the dry season transition and dry water-supply and involved increasing levels of supplementation (3.1, 3.7, 4.3, 4.9 and 5.5 kg of dry matter / animal / day ). Girolando five cows were used in the middle third of lactation, approximately six years of age and body weight of 500 kg were randomly divided into a 5x5 Latin square design. In both experiments, milk was weighed at 12, 13 and 14 days of each experimental period after the morning and afternoon milkings to measure the performance of animals. During the dry season, weight gains for the lambs were 0.017, -0.008, 0.024 and 0.077 kg day-1, respectively, for mineral supplements, energy, and multiple proteins. At the time four hours after supplementation, the pH values were 6.30, 6.40, 6.18 and 6.24, respectively, for the mineral supplements, energy and protein and the multiple values for ammonia were 10 , 57, 7.36, 21.58 and 24.50 mg dL-1 of rumen fluid, respectively, for mineral supplements, energy, and multiple proteins. In the rainy and dry transitional waters, were observed for average daily weight gains of 0.061, 0.080, 0.060 and 0.080 kg day-1, respectively, for the mineral mix, soybean meal, soybean and cottonseed. The average pH values were 6.16, 6.18, 6.25 and 6.23, respectively, for the mineral supplements, soybean meal, soybean and cottonseed with values for rumen ammonia nitrogen were 11, 10, 24.77, 22.31 and 29.37 mg dL-1 of rumen fluid, respectively, for mineral supplements, soybean meal, soybean and cottonseed. For supplemented calves during the dry weight gain of animals was 0.380, 0.600, 0.750 and 0.730 kg / day, respectively, for the mineral supplements, energy, protein and multiple verifying statistically significant difference between supplemented animals and receiving mineral mixture. For dairy cows in the rainy suplemetadas there was no effect of supplementation on milk production (P> 0.05), average daily production of 8.21 kg milk day-1 animal. For cows fed increasing levels of supplementation during periods of drought and water-dry transition, careful evaluation of the quality of pasture proved the necessity of using a supplement to avoid production losses during the period. For the supplementation levels proposed in this paper, the wet waste brewery can be used as an ingredient without causing significant effects on milk production, however, all levels of supplementation used generated positive gross margin. The mineral and protein supplements provided weight gain with lower production costs for lambs supplemented during the dry season. The use of energy supplement for lambs subjected to feed with low protein content reduces the weight gain of animals in relation to the supply of mineral mixture. For lambs supplemented during periods of water and water-dry transition, supplements of soybean meal and cottonseed increased weight gain at 8.75% compared to animals treated only with mineral mixture, lowering the age at slaughter of animals . For supplemented calves during the dry season supplementation produced multiple GMD 49.33% and 20.00% higher energy and mineral supplements. There was no difference in behavior of grazing (P> 0.05). Animals receiving the mineral mixture had time to 8.40 hours of grazing animal day-1. The multiple supplement provided better economic performance considering the sale of animals to 350 kg body weight. For dairy cows supplemented in the waters of the gross margins per kg milk produced for the supplements used were 0.54, 0.43, 0.38, 0.40 and 0.32 respectively for supplements minerals and energy supplied 2 and 4 kg and provided multiple of 2 and 4 kg animal-1 day. For dairy cows supplemented during periods of drought and drought-transition level of the water supply of 3.1 kg animal day provided the best gross margin between the amounts tested.